DNA testing for hypertrophic cardiomyopathy: a cost-effectiveness model. - Wordsworth, S; Leal, J; Blair, E; Legood, R; Thomson, K; Seller, A; Taylor, J; Watkins, H (2010)
Aims To explore the cost-effectiveness of alternative methods of screening family members for hypertrophic cardiomyopathy (HCM), the most common monogenic cardiac disorder and the most frequent cause of sudden cardiac death (SCD) in young people. Methods and results Economic decision model comparing cascade screening by genetic, as opposed to clinical methods. The incremental cost per life year saved was 14,397 euro for the cascade genetic compared with the cascade clinical approach. Genetic diagnostic strategies are more likely to be cost-effective than clinical tests alone. The costs for cascade molecular genetic testing were slightly higher than clinical testing in the short run, but this was largely because the genetic approach is more effective and identifies more individuals at risk. Conclusion The use of molecular genetic information in the diagnosis and management of HCM is a cost-effective approach to the primary prevention of SCD in these patients.